Enhancing Anthocyanin Extraction from Wine Lees: A Comprehensive Ultrasound-Assisted Optimization Study - Marcelo A. Umsza-Guez; Mercedes Vázquez-Espinosa; Nuria Chinchilla; María José Aliaño-González; Carolina Oliveira de Souza; Kodjovi Ayena; Gerardo Fernández Barbero; Miguel Palma; Ceferino Carrera (MDPI AG, 2023)
Wine lees, an important by-product of the wine industry, pose a major environmental problem due to the enormous quantities of solid-liquid waste that are discarded annually without defined applications. In this study, the optimization of a method based on a Box-Behnken design with surface response has been carried out to obtain extracts with high anthocyanin content and potent antioxidant activity. Six variables have been considered: %EtOH, temperature, amplitude, cycle, pH, and ratio. The developed method exhibited important repeatability properties and intermediate precision, with less than 5% CV being achieved. Furthermore, these novel methods were successfully applied to diverse wine lees samples sourced from Cabernet Sauvignon and Syrah varieties (Vitis vinifera), resulting in extracts enriched with significant anthocyanin content and noteworthy antioxidant activity. Additionally, this study evaluated the influence of grape variety, fermentation type (alcoholic or malolactic), and sample treatment on anthocyanin content and antioxidant activity, providing valuable insights for further research and application in various sectors. The potential applications of these high-quality extracts extend beyond the winemaking industry, holding promise for fields like medicine, pharmaceuticals, and nutraceuticals, thus promoting a circular economy and mitigating environmental contamination.